Media Dan Ict Dalam Problematika Dakwah - Bahrur Rosi (LP2M IAI Miftahul Ulum Pamekasan, 2018)
Da'wah is a noble activity in invite and exhorts others towards goodness, the methods and the material presented must be able to embrace and accommodate all the things required by the partners of da'wah in all its religious activities. Thus indirectly demanded the existence of adjustment always preach, from the method of delivery, the message or the medium used. The world preaching experience challenges that are increasingly heavy, especially the development of science and technology which is always directly proportional to the problems faced by mankind as a user of the product and the technology itself. The entanglement between the Da'wah with advances in science, technology and communication media very closely. It is because of the possibility to fill in between the two, in the sense of communication media can be a means for Da'wah to be able to spread the content of dakwahnya in order to reach out to places that are difficult to be accessed are not likely to accessible directly by their da'i. Such is the case with events, can be useful as a control over the content displayed by the communications media so that more unscrupulous and in accordance with the rules and customs that apply in the community.